A highly potent agonist to protease-activated receptor-2 reveals apical activation of the airway epithelium resulting in Ca(2+)-regulated ion conductance - Sherwood, Cara L. (American Physiological Society, 2014)
The airway epithelium provides a barrier that separates inhaled air and its various particulates from the underlying tissues. It provides key physiological functions in both sensing the environment and initiating appropriate innate immune defenses to protect the lung. Protease-activated receptor-2 (PAR(2)) is expressed both apically and basolaterally throughout the airway epithelium. One consequence of basolateral PAR(2) activation is the rapid, Ca(2+)-dependent ion flux that favors secretion in the normally absorptive airway epithelium. However, roles for apically expressed PAR(2) activation have not been demonstrated, in part due to the lack of specific, high-potency PAR(2) ligands. In the present study, we used the newly developed PAR(2) ligand 2at-LIGRLO(PEG(3)-Pam)-NH(2) in combination with well-differentiated, primary cultured airway epithelial cells from wild-type and PAR(2)(−/−) mice to examine the physiological role of PAR(2) in the conducting airway after apical activation. Using digital imaging microscopy of intracellular Ca(2+) concentration changes, we verified ligand potency on PAR(2) in primary cultured airway cells. Examination of airway epithelial tissue in an Ussing chamber showed that apical activation of PAR(2) by 2at-LIGRLO(PEG(3)-Pam)-NH(2) resulted in a transient decrease in transepithelial resistance that was due to increased apical ion efflux. We determined pharmacologically that this increase in ion conductance was through Ca(2+)-activated Cl(−) and large-conductance K(+) channels that were blocked with a Ca(2+)-activated Cl(−) channel inhibitor and clotrimazole, respectively. Stimulation of Cl(−) efflux via PAR(2) activation at the airway epithelial surface can increase airway surface liquid that would aid in clearing the airway of noxious inhaled agents.